2015
DOI: 10.1128/aem.00039-15
|View full text |Cite
|
Sign up to set email alerts
|

Metatranscriptomic Analysis of Diminutive Thiomargarita-Like Bacteria (“Candidatus Thiopilula” spp.) from Abyssal Cold Seeps of the Barbados Accretionary Prism

Abstract: Large sulfur-oxidizing bacteria in the family Beggiatoaceae are important players in the global sulfur cycle. This group contains members of the well-known genera Beggiatoa, Thioploca, and Thiomargarita but also recently identified and relatively unknown candidate taxa, including "Candidatus Thiopilula" spp. and "Ca. Thiophysa" spp. We discovered a population of "Ca. Thiopilula" spp. colonizing cold seeps near Barbados at a ϳ4.7-km water depth. The Barbados population consists of spherical cells that are morph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 93 publications
0
15
0
Order By: Relevance
“…While it is possible that living cells were present in void spaces within the crust, the lack of amplifiable DNA in rinsate fluids tested prior to DNA extraction from the crust, as well as the presence of partially mineralized Beggiatoa filaments in portions of the crust, suggest that at least some of the Beggiatoa DNA is coeval with barite precipitation. It is not surprising that Maribeggiatoa 16S rRNA gene sequences represent a relatively minor portion of the libraries here, given that numerous other studies have reported difficulties with amplifying 16S rRNA gene sequences from samples visibly dominated by Beggiatoa and related organisms in the family Beggiatoaceae (e.g., Sekar et al ., ; Salman et al ., ; Jones et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…While it is possible that living cells were present in void spaces within the crust, the lack of amplifiable DNA in rinsate fluids tested prior to DNA extraction from the crust, as well as the presence of partially mineralized Beggiatoa filaments in portions of the crust, suggest that at least some of the Beggiatoa DNA is coeval with barite precipitation. It is not surprising that Maribeggiatoa 16S rRNA gene sequences represent a relatively minor portion of the libraries here, given that numerous other studies have reported difficulties with amplifying 16S rRNA gene sequences from samples visibly dominated by Beggiatoa and related organisms in the family Beggiatoaceae (e.g., Sekar et al ., ; Salman et al ., ; Jones et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Thiopilula spp. (MacGregor et al, 2013;Jones et al, 2015) based on reverse operation in Nautilia profundicola (Hanson Figure 4 Schematics of 14 gammaproteobacterial genome bins with the metabolic potential to degrade hydrocarbons (Groups 1-4), and a schematic showing the genes GSC1 likely uses to encode for denitrification and sulfide oxidation (representative bin of Group 5: GSC1-3). Genes present are represented by black symbols; those missing are red.…”
Section: Upregulation Of Sulfur and Nitrogen Cycling Near The Wellheamentioning
confidence: 99%
“…Additional chemolithotrophic biomarkers involved in biogeochemical cycles included an enrichment of ferrous iron oxidisers (Acidomicrobiales) and the sulphur oxidising genus Thiopilula (Thiotrichales) in the oxic treatment30. Sulphur cycling in aquaculture systems is important as un-ionised dissolved hydrogen sulphide (H 2 S) is extremely toxic to many aquatic organisms, even at natural levels31.…”
Section: Discussionmentioning
confidence: 99%